Selective biosorption of lanthanides onto Galdieria sulphuraria. (March 2023) - Manfredi, C.; Amoruso, A.J.; Ciniglia, C.; Iovinella, M.; Palmieri, M.; Lubritto, C.; El Hassanin, A.; Davis, S.J.; Trifuoggi, M.
Abstract: The recovering of trivalent Lanthanides from aqueous solutions, by biosorption process onto Galdieria sulphuraria lifeless cells, was investigated. Potentiometry, UV–Vis, FTIR-ATR spectroscopy and SEM-EDS analysis were used. All the experiments were performed at 25 °C, in 0.5 M NaCl. Ln 3+ biosorption is greater in the 5–6 pH range with values ranging from 80 μmol/g to 130 μmol/g (dry weight). The adsorbed Ln 3+ ions can be recovered at higher acidity (pH<1) and the biosorbent can be reused. Specific molecular interactions between Ln 3+ ions and the functional groups on G. sulphuraria surface were highlighted. Particularly, proteins are involved if Ln 3+ =Pr 3+, Sm 3+, Eu 3+, Tb 3+, Dy 3+, Tm 3+, while Ce 3+, Ho 3+, Er 3+ form bonds with carbohydrates. Finally, both proteins and carbohydrates are involved if Gd 3+ and Yb 3+ . A Surface Complexation approach, with a good graphical fitting to potentiometric experimental collected data, was used to describe the biosorption mechanism. This study could be of great applicative utility for removing of trivalent actinides, from waste aqueous solutions, by biosorption. As well known the lanthanides were used as model to simulate the chemical behaviour of actinides in the same oxidation state. Graphical abstract: Image 1 Highlights: Lanthanides biosorption onto G. sulphuraria greater at pH > 4. Specific interactions Lanthanides-functional groups onto G. sulphuraria surface. Lanthanides biosorption mechanism onto G. sulphuraria explained by a Surface Complexation Model.